Impact of geometry on transport properties of armchair graphene nanoribbon heterojunction. (November 2017) - Zhang, Weixiang; Basaran, Cemal; Ragab, Tarek
Abstract: Electron transport properties of undoped armchair Graphene Nanoribbon Heterojunction (GNRHJ) has been studied using semi-empirical extended Hückel method (EH). A two-probe configuration device utilizing armchair GNRHJ has been proposed. It is shown that a potential barrier was formed at the heterojunction interface between semiconductor and semi-metal, which resemble the conventional Schottky barrier at the interface of semiconductor/metal. Transmission spectrum was analyzed at finite bias; and current-bias voltage characteristic relations were established. Results show that the I–V characteristics of the heterojunction have rectifying nature, with its rectification ratio affected by the geometric asymmetry of the heterojunction.